Results of broiler duck production in the example of a given farm - Molnár, Szilvia; Szőllősi, László (Animal welfare, Ethology and Housing Systems (AWETH), 2018)
The production of animals for slaughter in the Hungarian duck sector has doubled over the past decade. The objective of the study is to examine the physical efficiency and economic situation in broiler duck fattening through the example of a Hungarian farm. We have analyzed the trends of production parameters and costs in 2014-2016 by descriptive statistical methods and revealed the correlations among some factors. In the case of the examined farm, the average broiler duck cost was between 225 and 315 HUF/kg, on average 270.6 HUF/kg, where the key element is the feed and chick cost. In the meantime, the sales price dropped from 350 HUF/kg to 305 HUF/kg, resulting income decrease of average 41.7 HUF/kg. The results show that there is a moderate relationship between average cost and rearing period, daily weight gain, mortality and feed coversion ratio. On the other hand, weak relationship can be verified between average cost and final bodyweight.
Keywords: broiler duck production; physical efficiency; economic situation; correlation and regression analysis